(3GdebGdI GdNGeSI aj QSe GdBdGJ GdMGOKg Ydi JSWjM GdcQg cGdCSWQdGH GdTeGdi hGdLfhHi hGdRQbGdI hGdTcGRjI GdCQHGYs
(3ChdgG (B:s
(3GdHGH GdChd ai QSe GdCSWQdGH (B( 4 (3UaMGJ (B) s
(3BNQgG (B:s
(3hefJ Edi GdBNQ jMUd GdebfWQg GdeWdhHg jfHY HYOgG GdLOGhdkG ddgdGd GdTghQ GdYQHjg ef UaQ Edi Pi GdbYOg s
(3GdeSJYedI HGdNjW hGdeOi egOaI hgj eTJedI Ydi YOI CHhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B100 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B70) s
Keywords: (3Gdadcs